FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PADA USAHA MIKRO, KECIL DAN MENENGAH: (Studi pada Wajib Pajak Pemilik UMKM Di KPP Pontianak) - Reni Dwi Widyastuti (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2017)
This research is based on the way of Government in giving facilitation to people regarding the implementation of tax obligation by establishing Government Regulation No.462013. This research is purposed to explain influence variable of awareness tax., tax understanding,, Socialization Self Assesment System and the willingness Tax Payer is significant,to influence in tax payers compliance. Research method that isused is explanatory research with quantitative approach. Data collection method by using questionnaire for100 (Micro, Small and Medium Enterprise) MSME owners who are registered in tax office pratama Pontianak, West Kalimantan. Using descriptive analysis and multiple linear regression helped by SPSS software version 23, this study showed that the variable Awarenessof Tax, tax understanding, Self Assesment System dan the willingness of Tax Payer is significant, but Socialization not significantly influence in tax payers compliance.